Mystic pizza [videorecording (DVD)] - Petrie, Donald; Gish, Annabeth, 1973-; Roberts, Julia, 1967-; Taylor, Lili; D'Onofrio, Vincent; Moses, William R. (Contemporary classics (MGM Home Entertainment Inc.), 2001)
Three young women, waitresses at a pizza parlor in Mystic, Connecticut, spend a special summer discovering romance.